KETERLIBATAN DAN KEMAMPUAN TEKNIK PERSONAL PADA KINERJA SIA DENGAN PENDIDIKAN DAN PELATIHAN SEBAGAI VARIABEL MODERASI - Puspitasari, Ni Wayan Novia; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Computer-based accounting information system is very important applied in LPD to produce information in the form of relevant, accurate and timely financial statements. Good bad performance of an accounting information system can be seen from the user satisfaction of accounting information system itself. An information system will be successful if supported by several supporting factors. This study aimed to prove empirically the influence of user involvement and the ability of personal techniques on the performance of SIA with education and training as a moderation variable variable in LPD Gianyar District.This research is an associative quantitative research. The number of samples was taken by 66 respondents consisting of the head of LPD, employees of the administration and employees of the cashier based on non-probability sampling technique with purposive sampling method. Data were collected using survey method with questionnaire technique. Data analysis technique used is multiple linear regression test and interaction test of Moderated Regression Analysis (MRA). Based on the analysis result, it can be concluded that user involvement has positive and significant effect on accounting information system performance, personal technique ability have positive and significant influence on accounting information system performance, education and training unable to moderate influence of user involvement on accounting information system performance, and education and training Able to moderate the influence of personal technique ability on accounting information system performance in LPD Gianyar Subdistric.
Keywords: User involvement, personal technical capabilities, education and training, performance SIA